Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s12529-016-9622-3
|View full text |Cite
|
Sign up to set email alerts
|

Integral Health Status-Based Cluster Analysis in Moderate–Severe COPD Patients Identifies Three Clinical Phenotypes: Relevant for Treatment As Usual and Pulmonary Rehabilitation

Abstract: PurposeThe purposes of the study are to identify clinical phenotypes that reflect the level of adaptation to the disease and to examine whether these clinical phenotypes respond differently to treatment as usual (TAU) and pulmonary rehabilitation (PR), the latter with its strong emphasis on improving adaptation.MethodsClusters were identified by a cluster analysis using data on many subdomains of the four domains of health status (HS) (physiological functioning, functional impairment, symptoms and quality of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
(38 reference statements)
2
17
0
Order By: Relevance
“…Some recent clinical trials demonstrated the effectiveness of multidisciplinary pulmonary rehabilitation programs to reduce perceived fatigability. For instance, both a 3- and 12-week program have proven effective in reducing fatigue, in patients with sarcoidosis (Lingner et al, 2018 ) and COPD (Peters et al, 2017 ), respectively. However, in both studies fatigue was chosen as a secondary outcome and it is not known which component of these multimodal programs actually reduced fatigue.…”
Section: Perceived Fatigabilitymentioning
confidence: 99%
“…Some recent clinical trials demonstrated the effectiveness of multidisciplinary pulmonary rehabilitation programs to reduce perceived fatigability. For instance, both a 3- and 12-week program have proven effective in reducing fatigue, in patients with sarcoidosis (Lingner et al, 2018 ) and COPD (Peters et al, 2017 ), respectively. However, in both studies fatigue was chosen as a secondary outcome and it is not known which component of these multimodal programs actually reduced fatigue.…”
Section: Perceived Fatigabilitymentioning
confidence: 99%
“…60 Of note, pulmonary rehabilitation offers the most benefits to patients who score highest in anxiety and depression before starting rehabilitation, as well as patients who have not adapted (physically or psychologically) well to the disease. 23,27 Unfortunately, as noted above, these are also the same patients whom are least likely to finish rehabilita-tion even though they would derive the most benefit. Noticing a change in baseline, or the development of anxiety and depression, should warrant the involvement of palliative care and pulmonary rehabilitation in the patient's care if they are not already.…”
Section: Motivation For Patients To Complete Pulmonary Rehabilitationmentioning
confidence: 96%
“…24 Often, reported symptoms of the disease are not in line with expected results from physiological test results, which may result from poorly adapted beliefs and viewpoints of the disease. 23 One study was able to put moderate COPD suffers into two categories: patients who reported low impact of disease on health status and patients who reported high impact of disease on health status despite both populations having similar physiological impairments. 23 Although, both patient populations improved with pulmonary rehabilitation, the patients that subjectively experienced a higher impact of disease on their overall health status benefited most from a pulmonary rehabilitation program.…”
Section: Motivation For Patients To Complete Pulmonary Rehabilitationmentioning
confidence: 99%
“…Indeed, the effects of a conventional, home‐based exercise training programme on the performance of activities of daily life and daily symptoms beyond dyspnoea (i.e. anxiety, depression and fatigue) remain unknown, while this is clearly shown following a comprehensive, hospital‐based pulmonary rehabilitation programme . The home‐based approach does also not allow to truly target the training interventions to the possibilities/limitations of each individual patient.…”
Section: Home‐based Pulmonary Rehabilitationmentioning
confidence: 99%